Diseño de una envasadora automatizada de productos líquidos de la línea de bioseguridad en la Empresa Laboratorios Eufar S.A., Bogotá, Colombia (2023)
The project is carried out in order to innovate the production process of the company, increasing the productivity of disinfectant products, for this, the types of machine, the operation and operating conditions of the different types of liquids are taken into account. Once the aforementioned has been implemented, the calculations, selection of elements, construction materials and design proposal are made; seeking to comply and improve the packaging process of the products of the biosafety line. This project was developed in three stages: research, analysis of the components, search for alternatives, design of the components and preparation of the maintenance manual. Autodesk Inventor software was used for the development of each of the system components.